2010
DOI: 10.1162/jocn.2009.21389
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of the Testosterone–Aggression Relation: The Role of Orbitofrontal Cortex

Abstract: Testosterone plays a role in aggressive behavior, but the mechanisms remain unclear. The present study tested the hypothesis that testosterone influences aggression through the OFC, a region implicated in self-regulation and impulse control. In a decision-making paradigm in which people chose between aggression and monetary reward (the ultimatum game), testosterone was associated with increased aggression following social provocation (rejecting unfair offers). The effect of testosterone on aggression was expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
205
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(224 citation statements)
references
References 82 publications
12
205
0
2
Order By: Relevance
“…In our data, beliefs had no significant effect on rejection rates Evidence of a positive correlation between baseline T levels and low offer rejections was found in two previous studies (Burnham, 2007;Mehta and Beer, 2010). We reproduced their analysis using responses in the placebo condition and found no significant difference in (log) baseline T levels between subjects who accepted 2GBP offers, and those who rejected them, although the difference was in the same direction as the previous reports (t(30) = 0.26, one-sided p = 0.4, d = 0.10, 95% C.I.…”
Section: Beliefs and Baseline Tsupporting
confidence: 62%
See 3 more Smart Citations
“…In our data, beliefs had no significant effect on rejection rates Evidence of a positive correlation between baseline T levels and low offer rejections was found in two previous studies (Burnham, 2007;Mehta and Beer, 2010). We reproduced their analysis using responses in the placebo condition and found no significant difference in (log) baseline T levels between subjects who accepted 2GBP offers, and those who rejected them, although the difference was in the same direction as the previous reports (t(30) = 0.26, one-sided p = 0.4, d = 0.10, 95% C.I.…”
Section: Beliefs and Baseline Tsupporting
confidence: 62%
“…Alternatively, Bayes factors can be computed to estimate the odds that the null model is correct relative to alternative models that assume a positive treatment effect. Basing our prior on the positive correlations between basal T and rejection rates reported in earlier studies (Burnham, 2007;Mehta and Beer, 2010), our evidence yields Bayes factors ranging from 4.84 to 28.29, which, according to commonly used evidence categories, constitute substantial and strong evidence in favor of the null model, respectively (see supplementary information).…”
Section: T Administration and Ultimatum Rejectionssupporting
confidence: 52%
See 2 more Smart Citations
“…Two correlational studies have reported that men and women with relatively high baseline concentrations of testosterone are more likely to reject unfair offers [38,39]. In contrast, pharmacological challenge research in both men and women have not found these effects of testosterone on rejection behavior in the ultimatum game [40,41,42,22].…”
Section: Testosterone and The Ultimatum Gamementioning
confidence: 99%